Determinants of Maternal Home Delivery in Nigeria: Evidence for Targeted Health Policy Interventions - Ayegboyin, Matthew (Darul Yasin Al Sys, 2025)
Maternal mortality remains a critical public health concern globally, with Nigeria bearing the highest burden of avoidable maternal deaths despite a global decline in the maternal mortality ratio. A significant proportion of these deaths occur during childbirth, often linked to home deliveries. Although several maternal health policies and programs have been introduced to promote facility-based deliveries, a large number of Nigerian women continue to give birth at home. This study investigates the determinants of home delivery among Nigerian women to inform health policy aimed at reducing maternal mortality. Utilizing data from the 2018 Nigeria Demographic and Health Survey (NDHS), a filtered sample of 41,821 women aged 15–49 was analyzed using SPSS version 27. Descriptive and bivariate statistical techniques were employed to identify key influencing factors. The findings reveal that home delivery is most prevalent among teenage mothers (63.1%), uneducated women (82.4%), the poorest socioeconomic group (75.7%), rural residents (63.8%), and women in the northwest region (83.4%). Language barriers also emerged as a significant determinant of home delivery. The study recommends the development of state-specific policies to train Traditional Birth Attendants (TBAs) at no cost, particularly in rural and underserved communities, to improve maternal health outcomes and reduce reliance on unsafe home deliveries.